2020
DOI: 10.1093/braincomms/fcaa101
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 deficiency accelerates hippocampal synaptic remodelling and age-related deficits in learning and memory

Abstract: A healthy mitochondrial network is essential for the maintenance of neuronal synaptic integrity. Mitochondrial and metabolic dysfunction contributes to the pathogenesis of many neurodegenerative diseases including dementia. OPA1 is the master regulator of mitochondrial fusion and fission and is likely to play an important role during neurodegenerative events. To explore this, we quantified hippocampal dendritic and synaptic integrity and the learning and memory performance of aged Opa1 haploinsufficient mice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 97 publications
2
7
0
Order By: Relevance
“…Opa1 K301A -expressing nematodes display fewer SNB-1::GFP puncta and larger synaptic regions in GABAergic motor neurons (Fig. 5e–g ), a finding consistent with the observed reduction in synapses in mammalian cortical neurons where Opa1 was ablated [ 30 ] and in RGCs and hippocampal neurons of an ADOA mouse model [ 44 , 45 ].
Fig.
…”
Section: Resultssupporting
confidence: 81%
“…Opa1 K301A -expressing nematodes display fewer SNB-1::GFP puncta and larger synaptic regions in GABAergic motor neurons (Fig. 5e–g ), a finding consistent with the observed reduction in synapses in mammalian cortical neurons where Opa1 was ablated [ 30 ] and in RGCs and hippocampal neurons of an ADOA mouse model [ 44 , 45 ].
Fig.
…”
Section: Resultssupporting
confidence: 81%
“…In agreement, these animals, like most DOA patients, display late-onset visual deficits due to optic nerve degeneration (Lenaers et al, 2021). Using another DOA mouse model, a recent study reported cognitive impairments at older age (over 14 months), when visual impairments are described, precluding reliable determination of the cognitive profile of these mice at this age (Bevan et al, 2020).…”
Section: Discussionmentioning
confidence: 64%
“…CA1 neurons of Opa1 +/− mice display reduced spine density. Interestingly, Opa1 +/− CA1 neurons of female mice have significantly shorter dendrites and lower ATP production compared with male mice, which together contribute to a distinct form of memory loss [148,149]. The lack of Opa1 has been demonstrated to induce mitochondrial respiratory defects and mitochondrial fragmentation, as well as a reduction in mitochondrial density of neuronal axons in Drosophila larvae.…”
Section: Mitochondrial Fusion and Fission In The Nervous Systemmentioning
confidence: 99%